Research on the spoilage characteristics of whole-plant corn silage inoculated with Clostridium beijerinckii SHZ-8 - Yang, Fan; Fu, Dongqing; Yu, Xue; Lv, Jiaying; Ma, Chunhui (Frontiers in Microbiology, 2025)
Maize silage serves as a crucial feed resource for ruminants, yet its quality is frequently compromised during storage by spoilage-associated microbial activity. Clostridium species, particularly Clostridium beijerinckii, are known to induce spoilage by altering fermentation pathways. This study aimed to elucidate the effects of inoculation with C. beijerinckii SHZ-8 on microbial succession, metabolite profiles, and fermentation quality in whole-crop maize silage throughout the spoilage process. Silage samples were prepared with and without C. beijerinckii SHZ-8 inoculation. Microbial community dynamics were assessed via 16S rDNA sequencing, while metabolite alterations were characterized using untargeted metabolomics. Fermentation parameters including nutrient composition, bacterial counts, and organic acid concentrations and ratios were also determined. Correlation analyses between key metabolites and core microbial taxa were conducted. Inoculation with C. beijerinckii SHZ-8 significantly reduced dry matter content by 5.28% (p < 0.01) and lactic acid bacteria counts by 54.51% (p < 0.01), while increasing Clostridium abundance by 3.40 log₁₀ CFU/g FW (p < 0.01). The dominant fermentation mode shifted from homofermentation to heterofermentation, accompanied by an 81.6% decrease in the lactate-to-acetate ratio (p < 0.01). D-galacturonic acid levels exhibited a strong positive correlation with C. beijerinckii SHZ-8 abundance (R2 = 0.87, p < 0.01), suggesting its potential as a biomarker for Clostridium overgrowth. Notably, octanal and D-galacturonic acid emerged as candidate biomarkers in the inoculated group, providing a basis for the development of silage quality monitoring tools. These findings offer valuable insights for improving silage management strategies, enhancing feed preservation, and advancing the sustainability of livestock production.